2007
DOI: 10.17221/2011-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-phenoxyethanol anaesthesia on sheatfish (Silurus glanis L.)

Abstract: The aim of the study was to investigate the acute toxicity of 2-phenoxyethanol to sheatfish, and using the values of haematological and biochemical profiles of blood and histological tissue examinations to assess the effects of the fish exposure to that anaesthetic. The values of acute toxicity of 2-phenoxyethanol to sheatfish were found to be 10minLC50 0.77 ml/l, 10minLC0.1 0.42 ml/l, 10minLC99.9 1.90 ml/l, 96hLC50 0.29 ml/l, 96hLC0.1 0.20 ml/l, and 96hLC99.9 0.41 ml/l. The 10-min exposure to 2-phenoxyethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
5
33
1
1
Order By: Relevance
“…However, our data differ with findings reported in other species of fish. Velisek et al (2007) observed changes in MCHC and PCV with 2-phenoxyethanol anaesthesia on European catfish. Similar results were obtained by Kristan et al (2012) in their study of the effects of anaesthesia on pikeperch (Sander lucioperca).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…However, our data differ with findings reported in other species of fish. Velisek et al (2007) observed changes in MCHC and PCV with 2-phenoxyethanol anaesthesia on European catfish. Similar results were obtained by Kristan et al (2012) in their study of the effects of anaesthesia on pikeperch (Sander lucioperca).…”
Section: Discussionmentioning
confidence: 74%
“…Gomulka et al (2008) also reported decreased ammonia levels in Siberian sturgeon (Acipenser baerii) after eugenol (0.075 ml/l) and MS 222 (125 mg/l) anaesthesia. No changes in the levels of ammonia in rainbow trout, carp, European catfish, or perch following clove oil (30 mg/l) and 2-phenoxyethanol (0.30 ml/l) anaesthesia were observed by Velisek and Svobodova (2004a), and Velisek et al (2005bVelisek et al ( , 2007Velisek et al ( , 2009). Our differing results may be associated with the concentrations of the tested substances and the fish species used.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations